Politeness Strategies Used by Anies Baswedan in the Interview on Humanities in Southeast Asia - Rahman, Farisa; Rangkuti, Rahmadsyah; Mono, Umar (LingPoet: Journal of Linguistics and Literary Research, 2022)
This study applied a qualitative descriptive approach that establishes the requirement that a study must be carried out on the basis of existing facts. This study aims to examine the politeness strategies used by Anies Baswedan in the interview on humanities in Southeast Asia. The source of data of this study was obtained from youtube. This research data is in the form of phrases and clauses which contained politeness strategies. The collected data is assessed using Brown and Levinson's Politeness Strategies theory to find out the types of politeness strategy and its sub-strategies. This study applies a pragmatic study. After analyzing the data, the researchers concluded that there are three types of politeness strategies found in the Interview on Humanities in Southeast Asia. These three types of politeness strategies are: Bald on record, positive politeness, and negative politeness